The public perception and the role of Pusat Perkembangan Strategik & Hubungan Korporat (PPSHK): study in USIM / Siti Asliza Noor Marini Hashim - Hashim, Siti Asliza Noor Marini (2009)
Public Perception and Public Relation is one of the factors it will affect to the organizations including education institution. The good strategy should be identify to achieving the company objective and goals, the strategy that can be employed in this case likes promotion, co-operation all unit in that organization, medium used like printed media and media electronic and etc. in this case study has recommendation, the recommendation may come from suggestion the authors and from my observation, experience, and discussion between my supervisors. The recommendation also has come from the suggestion of that organization. This recommendation can overcome the problem faced by USIM and at the same time it can enhance the public perception towards USIM. This project paper which entitle “The Public Perception and The Role of Pusat Perkembangan Strategik & Hubungan Korporat: Study in University Science Islam Malaysia (USIM) “purposely to study what the public perception toward USIM and the effectiveness role Pusat Perkembangan Strategik & Hubungan Korporat (PPSHK) at USIM. From the study, the case can identify the public perception towards USIM, based on name “USIM” is a commercialize name, but if ask the public some of them say them are never heard this institution, have say is it that private university and also have some of them thought this institution branch of UIA. PPSHK role is important because as a front counter for USIM and it affected to the image and university reputation. This report outline the introduction, literature review, finding and analysis, conclusions and recommendation based on the journal and observation during the practical trainee at USIM, Nilai Campus, Negeri Sembilan.